Optimiza of cultural conditions in liquid media of Schizochytrium sp. PQ6 isolated from Phu Quoc island, Kien Giang province - Hoai Thu, Ngo Thi; Lan Anh, Hoang Thi; Hong, Danng Diem (Academia Journal of Biology, 2014)
Optimiza of cultural conditions in liquid media of Schizochytrium sp. PQ6 isolated from Phu Quoc island, Kien Giang province